National and social character of the conflict of dramatic works on the theme of ZHeltoksan (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article summarizes the dramatic works written on the topic of Zheltoksan, their genre features are considered. The article contains dramatic works written on the topic of Zheltoksan and examines their genre features. There are quite a few dramatic works on this topic. In the dramatic works of M. Shakhanov and Sh. Aitmatova, I.Saparbayeva, S.Dosanova, B.Mukai, M.Baigut, U.Akhmeta the main characters of the works contain the main signs and characteristics of historical reality. Their conflicting fate is successfully reflected in dramatic works, where the conflict is pronounced. All dramatic plays on the theme of yolkson have a common image of the hero Yolkson. The image of these heroes is the result of the struggle of the Kazakh people against colonialism and aggression, various forms of expansion. The image of these heroes was created on the basis of various conflicts between society and people.They are valuable primarily as historical characters, not as dramatic characters. The relevance of the article lies in the first generalized analysis of dramatic works on this topic.
Keywords: literature, Zheltoksan event, drama, main character, historical truth